Physical Education Learning Management Sports And Health School Extraordinary C Karesidenan Banyumas (Journal of Physical Education and Sports, 2021)
The problem in this research is the provision of the same material in each class, where physical education learning activities in schools are divided into two, namely upper and lower classes, the upper class starts from grade VII - IX SMPLB and X-XII SMALB while the lower class starts from grade I-VI SDLB. Research using evaluative qualitative approach using the help of Countenance Stake evaluationmodel. Data analysis techniques use a four-component cycle that takes place continuously between data collection, data reduction, data presentation and data withdrawal and verification. The results showed: (1) Planning of physical education learning sports and school health is outstanding C Karesidenan Banyumas has good learningplanning; (2) The implementation of physical education learning of sports and school health is extraordinary C Karesidenan Banyumas has been carried out properly in accordance with theteaching; (3) Assessment of physical education learning of sports and school health is outstanding C in Banyumas District is carried out properly in accordance with the assessment guidelines.